Automated 24-h surveys of flower-visiting communities reveal temporal complementarities and overlaps among strawberry pollinators - Elsa Blareau; Clarisse Gabard; Clémence Riva; Isabelle Dajoz; Fabrice Requier (Global Ecology and Conservation, 2025)
Differences in flower visitor functional traits, such as time of day of activity or foraging behaviour, allow for complementary contributions to pollination services. These traits vary among flower visitors due both to differing physiological constraints and responses to floral resource diversity and availability. However, little is known about the temporal and behavioural complementarities of flower visitors in terms of their daily activity. We carried out automated 24-h video surveys to track strawberry flower visitors in three study sites in the region of Paris (France) with different surrounding land-use composition. We tested whether different flower visitor groups were active at different times of day (i.e. temporal complementarity vs. overlap), and whether foraging behaviour varied among groups and across the day. We found that most pollinators were active during the day, with ants reported as the main nocturnal flower visitors. Moreover, we found complementarity in the temporal activity of flower visitors in the least urbanised site. In contrast, in the more densely urbanised sites, a single peak of activity occurred during the afternoon, with dominance of honey bees, indicating overlap in temporal niche. We also found that the flower-visit duration varied substantially among pollinator groups, sites, and over the course of the day. These results emphasise how pollinator community functional complementarities can be context dependent. Indeed, currant knowledge is based mainly on diurnal observations of pollinator communities, which could bias our understanding of the relations between pollinator community composition and their contributions to pollination services.